A Simplified Geometric Channel Model for Mobile-to-Mobile Communications - Baltzis, Konstantinos B. (Společnost pro radioelektronické inženýrství, 2011)
In Mobile-to-Mobile (M2M) communications, the communicating nodes are surrounded by scatterers and equipped with low elevation antennas. This paper proposes a simple 2-D geometric scattering model for M2M channels. The model is also applicable in cellular systems when we employ low height base station antennas. In our approach, the scatterers are uniformly distributed in ellipses with arbitrary size and orientation around each communicating node. We provide simple formulas for the calculation of the angular spread and delay variation of the propagating signal. Simulation results verify the accuracy of the model. In order to validate the generalization of the approach, we compare it against notable models in the literature. As an application example, we investigate the impact of scatterer distribution and separation between mobiles on the angle and time of arrival statistics of the multipaths.
Keywords: Angle of arrival; time of arrival; regular-shaped Geometrical-Based Stochastic Models; scattering; Mobile-to-Mobile channel